Correlation between Epilepsy Self-Management Behaviors and Seizure Frequency among Patients with Epilepsy in Iran Epilepsy Association - Safoura Yadollahi; Tahere Ashktorab; Farid Zayeri; Zahra Safavibayat (Zanjan University of Medical Sciences and Health Services, 2015)
Background and Objectives: Epilepsy is a chronic condition results in seizure and leads to debilitating conditions in patients. Epilepsy self-management behaviors include activities to manage the disease. The aim of this study was to assess self-management behaviors and its correlation with seizure frequency in patients with epilepsy. Materials and Methods: In this correlation study, 120 patients with epilepsy were selected from Iran Epilepsy Association using convenience sampling method. Data were collected using a demographic checklist, Dilorio´s epilepsy self-management behaviors scale and a checklist to record the number of seizures. Data were analyzed in the SPSS-16 using the correlation coefficient. Results: The mean score of the self-management behaviors was 118.05±21.54. The highest score was in the area of seizure management (79.9) and the lowest score was in the area of drug management (57.56). There was a significant relationship between the epilepsy self-management behaviors and the frequency of seizures in patients with epilepsy (r=-0.3 P<0.001). Conclusion: The frequency of self-management behaviors was moderate. In patients with higher self-management behaviors score, seizures frequency was found to be lower.